The two-step purification method ViREn identifies a single NSUN6-mediated 5-methylcytosine modification promoting dengue virus RNA genome turnover - Wu, Chia Ching; Naarmann-de Vries, Isabel S.; Hartmann, Jonas; Nidoieva, Zarina; Kopietz, Kevin; Marchand, Virginie; Özrendeci, Zeynep; Lindner, Doris; Schelchshorn, Sophia; Flad, Sophia; Frye, Michaela; Papavasiliou, Nina; et al. (Nucleic acids research, 2026)
Chemical modifications on cellular and viral RNAs are new layers of post-transcriptional regulation of cellular processes, including RNA stability and translation. Although advances in analytical methods have improved the detection of RNA modifications, precise mapping at single-base resolution remains challenging. Requirements for sensitivity and purity limit accuracy and reproducibility, especially for low abundant viral RNAs extracted from infected cells. Here, we report a two-step method, ViREn, for the enrichment of the genomic RNA (gRNA) of dengue virus (DENV), a positive-sense single-stranded RNA virus. This approach enabled the preparation of gRNA with significantly increased purity and led to the identification of a single high-confidence 5-methylcytosine (m5C) site in DENV gRNA at position 1218. This finding was orthogonally validated by Illumina-based bisulfite sequencing and by Nanopore Oxford Technologies direct RNA sequencing. Strikingly, m5C1218 was detected exclusively in gRNA extracted from infected cells but not in gRNA extracted from viral particles. We identified NSUN6 as the host methyltransferase catalyzing this modification and demonstrated a role for m5C in regulating DENV gRNA turnover. ViREn thus enables the mapping of m5C on low-abundance viral gRNA with unprecedented precision and sensitivity and facilitates future mechanistic studies into the role of RNA modifications in virus replication.